GAMBARAN PEMERIKSAAN INPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVIKS DI HOTSPOT JALAN TUANKU TAMBUSAI KECAMATAN SUKAJADI PEKANBARU - Novri, Dhini Aiyuli; sofian, Amru; Fidiawati, Wiwit Ade (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is the third most frequent cancer in women in Indonesia. Indirect female sex worker are in high risk for having cervical cancer. World Health Organization had recommended an alternative approach for developing countries with down staging concept of cervical malignancy with visual inspection with acetic acid (VIA) to detect cervical precancerous lesion. This research was carried out at hotspot Tuanku Tambusai Street, Pekanbaru aimed to describe the characteritics of respondent and to detect displastic cervical epithelial cells with VIA. The result showed from 31 indirect female sex worker, 52 % were diagnosed with positive acetowhite appereance (positive VIA). Conclusion of the study that displastic cervical epithelial cells of indirect female sex worker who has high risk for having cervical cancer should be reffered for further follow up.Keywords: Visual inspection with acetic acid, Cervical cancer, Cervical precancerous lesion, Indirect female sex worker.